Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Minat Beli Konsumen Thrifting Yang Di Moderasi Brand Awareness - Hamonangan, Mordekhai; Lukiyana, Lukiyana (Fakultas Ekonomi Universitas Kadiri, 2024)
This investigation aims to test and assess the impact of service quality and product quality on purchase intention, considering brand awareness as a moderating factor. The data collection methodology involved using a simple random sampling approach through the distribution of research questionnaires. The research findings show a positive and statistically significant correlation between quality and purchase intention. The impact of product quality on purchase intention is positive and statistically significant. The impact of brand awareness on purchase intention is positive and statistically significant. Customers' familiarity with a brand may decrease over time, but it remains influential. It can be a moderating factor in the relationship between service quality and the likelihood of purchasing. Improving and regulating the relationship between product quality and purchase intention can be facilitated by increasing brand awareness.